Early specialized palliative care for patients with metastatic lung cancer receiving chemotherapy: a feasibility study of a nurse-led screening-triggered programme. (26th January 2022) - Matsumoto, Yoshihisa; Umemura, Shigeki; Okizaki, Ayumi; Fujisawa, Daisuke; Kobayashi, Naoko; Tanaka, Yuko; Sasaki, Chiyuki; Shimizu, Ken; Ogawa, Asao; Kinoshita, Hiroya; Uchitomi, Yosuke; Yoshiuchi, Kazuhiro; et al.
Abstract: Background: Strategies to implement early specialized palliative care have not yet been established. The present study investigated the feasibility of a nurse-led, screening-triggered early specialized palliative care intervention programme and obtained data to design a randomized controlled trial. Methods: Patients with metastatic lung cancer undergoing first-line platinum-based chemotherapy were eligible. The intervention consisted of (1) a questionnaire-based screening programme and (2) advanced-level nurse counselling and care coordination with interdisciplinary team approach. The primary endpoint was the completion rate of the assessment questionnaire after the second course of first-line chemotherapy (T2). Secondary endpoints included changes in Functional Assessment of Cancer Therapy-Lung scores, depression and anxiety rates based on the Patient Health Questionnaire 9 and the Hospital Anxiety and Depression Scale, and the contents of specialized palliative care. Results: A total of 50 patients were enrolled between August 2012 and March 2014. Median age was 66 years (range, 40–78 year) and 84% were male. A total of 38 patients had stage IV non-small cell lung carcinoma and 12 had extensive disease small-cell lung carcinoma. The completion rate was 70% (95% confidence interval 56.0–81.0). The median duration between baseline and T2 was 53 days. Improvement from baseline were observed at T2 in Functional Assessment of Cancer Therapy-Lung scores (86.0 ± 18.1 vs 94.9 ± 18.2, P = 0.057), depression (16.0 vs 5.7%; P = 0.26) and anxiety (32.0 vs 22.9%; P = 0.65); however, these results were not statistically significant. Conclusions: This early specialized palliative care intervention is feasible and could be useful in improving patients' quality of life. The present results justify the initiation of a randomized control trial. Abstract : This is the feasibility study of a nurse-led screening-triggered palliative care programme integrated into standard cancer treatment even from the early phase of the illness in advanced lung cancer patients.